Laparoscopic Versus Open Adhesiolysis for Small Bowel Obstruction: A Single-Center Retrospective Case-Control Study. Issue 3 (June 2016) - Lin, Hao; Li, Jiante; Xie, Zhiyuan; Zhang, Wentao; Lv, Xiaopeng
Abstract : Aim: This study is to investigate the short-term outcomes of small bowel obstruction (SBO) patients undergoing laparoscopic versus open adhesiolysis. Patients and Methods: A total of 202 patients with SBO were enrolled in this study. The patients underwent either laparoscopic (n=101) or open adhesiolysis (n=101). The primary end point was 30-day overall complications and secondary outcomes included major complications such as superficial and deep wound infections, mortality, postoperative length of stay, and operative time. Results: There was no statistically significant difference in the demographic parameters between laparoscopic and open adhesiolysis populations. The mean operative time for laparoscopic adhesiolysis was significantly less than open adhesiolysis (70±34.2 vs. 101±50.2, P =0.01). Statistically significant differences in flatus day (3.5±1.2 vs. 4.5±1.8, P =0.035) and postoperative hospital stay (6.4±2.1 vs. 7.2±2.9, P =0.041) were identified in favor of laparoscopic group, whereas the medical expenses for both groups were not different (31012.0±3412.9 vs. 30029.0±3100.9, P >0.05). The overall complications for open and laparoscopic group were 19.8% and 9.9%, respectively ( P =0.048). The important factors that led to a significantly lower overall complications rate in laparoscopic group might result from the lower wound (9.9% vs. 2.0%, P =0.017) and infectious (10.9% vs. 3.0%, P =0.027) complications. Conclusions: The laparoscopic approach for SBO is feasible because of its fewer complications and hospital stay.